Au modified PrFeO3 with hollow tubular structure can be efficient sensing material for H2S detection - Zhang, Heng; Xiao, Jing; Chen, Jun; Zhang, Lian; Zhang, Yi; Jin, Pan (Frontiers in Bioengineering and Biotechnology, 2022)
The H2S concentration in exhaled breath increases marginally with the progress of periodontal disease, and H2S is considered to be one of the most important gases related to meat and seafood decomposition; however, the concentration of H2S is low and difficult to detect in such scenarios. In this study, Au–PrFeO3 nanocrystalline powders with high specific surface areas and porosities were prepared using an electrospinning method. Our experimental results show that loading Au on the material provides an effective way to increase its gas sensitivity. Au doping can decrease the material’s resistance by adjusting its energy band, allowing more oxygen ions to be adsorbed onto the material’s surface due to a spillover effect. Compared with pure PrFeO3, the response of 3 wt% Au–PrFeO3 is improved by more than 10 times, and the response time is more than 10 seconds shorter. In addition, the concentration of H2S due to the decomposition of shrimp was detected using the designed gas sensor, where the error was less than 15%, compared with that obtained using a GC-MS method. This study fully demonstrates the potential of Au–PrFeO3 for H2S concentration detection.